Polarity determination in the Drosophila eye: a novel role for unpaired and JAK/STAT signaling. - Zeidler, M.P.; Perrimon, N.; Strutt, D.I. (Genes & Development, 1999)
The JAK/STAT signaling pathway is required for many processes including cytokine signaling, hematopoiesis, gliagenesis, and Drosophila segmentation. In this report we present evidence demonstrating that the JAK/STAT pathway is also central to the establishment of planar polarity during Drosophila eye development. We show that a localized source of the pathway ligand, Unpaired, is present at the midline of the developing eye, which is capable of activating the JAK/STAT pathway over long distances. A gradient of JAK/STAT activity across the DV axis of the eye regulates ommatidial polarity via an unidentified second signal. Additionally, localized Unpaired influences the position of the equator via repression of mirror.